Proceedings of the Third International Conference on Learning Analytics and Knowledge 2013
DOI: 10.1145/2460296.2460309
|View full text |Cite
|
Sign up to set email alerts
|

Understanding promotions in a case study of student blogging

Abstract: Promoting blog content is a social activity; it is a means of communicating one student's appreciation of another student's work. This paper explores the feasibility of using student promotions of content, in a blogosphere, to identify quality content, and implications for instructors. We show that students actively and voluntarily promote content, use promotion data to select which posts to read, and with considerable accuracy identify quality material. We explore the benefits of knowing which students are go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Equally important is promoting the emergence of crowd-based reciprocal teaching by supporting dialogue and collaboration between peers as reciprocal teachers. Early evidence has emerged as to the capacity of learners to provide reciprocal teaching services, such as identifying quality material, guiding selection of what to read, identifying quality posts, and evaluating peers (Gunnarsson & Alterman, 2013, 2014. The work of others (Sadler, 2010) has suggested that engagement with exemplars and in dialogues about holistic quality can assi st learners, over time, to develop the tacit knowledge of unseen, unarticul ated knowhow that marks out an expert from an inexpert appraiser, and the teacher from the taught.…”
Section: Implications Of C-sl Capability For Mooc Designmentioning
confidence: 99%
“…Equally important is promoting the emergence of crowd-based reciprocal teaching by supporting dialogue and collaboration between peers as reciprocal teachers. Early evidence has emerged as to the capacity of learners to provide reciprocal teaching services, such as identifying quality material, guiding selection of what to read, identifying quality posts, and evaluating peers (Gunnarsson & Alterman, 2013, 2014. The work of others (Sadler, 2010) has suggested that engagement with exemplars and in dialogues about holistic quality can assi st learners, over time, to develop the tacit knowledge of unseen, unarticul ated knowhow that marks out an expert from an inexpert appraiser, and the teacher from the taught.…”
Section: Implications Of C-sl Capability For Mooc Designmentioning
confidence: 99%
“…The promotion feature is simple to use and easy to implement and understand. Studies have shown that students will actively promote content; promoted content tends to be of higher quality; the promotion data is used to navigate; and some students are reliably better at assessing quality than others (Gunnarsson and Alterman, 2014;Gunnarsson and Alterman, 2013).…”
Section: Heuristicsmentioning
confidence: 99%